The Variation of Swear Word â€œKlengâ€ and its Flexibility in Denpasar - I Made Astu Mahayana; Agus Darma Yoga Pratama (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The paper investigates the Balinese swear word kleng and its variations used by teenagers in Denpasar. They use this word in various types whose functions differ depending on the context of the situation. Basically, kleng is a swear word used to insult others or show anger. However, some people can use this word to show intimacy toward others and humour. This study investigates variations of the word kleng and its flexibility used by the young generation in Denpasar based on linguistic anthropology. This research is descriptive research through a qualitative approach. The data were collected from conversations of the young generation in several coffee shops in Denpasar. Besides, the social media platforms, namely Instagram and Tiktok, were also used as secondary data. Based on the results, this research found several variations of the word kleng, including naskleng, kle, klieng, klie, nanas klengkeng leci, and klek. These variations reflect psychological, social, and linguistic functions. This research underscores language's importance in reflecting evolving cultures, feelings, and social dynamics, offering insights into an ever-changing society.